Marriage Postponement Among Female Students at UIN Siber Syekh Nurjati Cirebon: A Rational Choice Perspective - Mohamad Rana; Edy Setyawan; Akhmad Shodikin; Hanida Nuraisyah (International Journal of Nusantara Islam, 2026)
This study examines the factors that lead female students at UIN Siber Syekh Nurjati Cirebon to postpone marriage and analyzes these decisions through the lens of Rational Choice Theory. Using a qualitative, phenomenological approach, the study involved 10 unmarried final-semester female students purposively selected from several study programs. Data were collected through in-depth interviews, participatory observation, and supporting documentation, and were analyzed using thematic analysis, with triangulation employed to enhance trustworthiness. The findings show that marriage postponement is primarily driven by educational aspirations, career orientation, economic readiness, psychosocial maturity, and family expectations. They further indicate that female students do not view delayed marriage as a rejection of marriage itself, but rather as a rational and strategic response to the competing demands of self-development, financial stability, and future family life. From the perspective of Rational Choice Theory, marriage postponement can be understood as a negotiated decision through which students weigh the costs, benefits, opportunities, and constraints associated with marriage timing. The study suggests that delayed marriage among female students reflects changing aspirations and forms of agency among educated Muslim women in contemporary Indonesia. These findings have important implications for women’s empowerment, premarital education, and student support policies within Islamic higher education institutions.